Synthesis of Betacyanin-Grafted Inulin as a Colon Cancer Therapeutic: In Silico Evaluation via Molecular Docking and Molecular Dynamics - Azhar, Minda; Putri, Selvi Apriliana; Maksum, Iman Permana; Ananda, Rendi; Ikhsan, Muhammad Habibul; Faridah, Anni; Effendi, Hastria; Wahyuni, Fatma Sri (Trends in Sciences, 2026)
Inulin is a fructan polymer composed of β-2,1-linked fructose units, known for its resistance to digestion in the upper gastrointestinal tract and selective fermentation by probiotics in the colon. This property makes inulin a promising candidate for colon-targeted drug delivery. In this study, betacyanin-grafted inulin was synthesized and evaluated for its potential as a colon cancer therapeutic, targeting Cyclooxygenase-2 (COX-2), a key enzyme involved in inflammation and tumor progression. This study aims to synthesize betacyanin-grafted inulin, characterize its structural and optical properties using Fourier Transform Infrared (FTIR) and Ultraviolet-Visible (UV-Vis) spectroscopy, assess its antioxidant activity, and evaluate its interaction with the COX-2 receptor through in silico molecular docking and molecular dynamics analysis. The grafting process was conducted under inert conditions using betacyanin masses of 0.2, 0.4 and 0.6 g. The optimal formulation was identified at 0.4 g, yielding a bound betacyanin content of 582 mg BAE/g. Structural characterization using FTIR revealed absorption bands at 1,540 - 1,418 cm⁻¹ (C=C aromatic stretching) and 1,670 cm⁻¹ (N-H bending), confirming the presence of betalamic acid. UV-Vis spectroscopy showed a maximum absorption at 530 nm, consistent with betacyanin’s chromophore. Antioxidant assays demonstrated that the 0.4 g variation retained significant activity (35.08 mg/L), indicating that betacyanin remained bioactive post-grafting. In silico molecular docking and dynamics simulations revealed that betanin, the major betacyanin component, exhibited strong binding affinity (−8.6 kcal/mol) and favorable binding free energy (−20.3618 kcal/mol) at the COX-2 active site, suggesting stable interaction and potential inhibitory effects. ADMET analysis further supported the therapeutic viability of betacyanin, showing optimal absorption, wide distribution, and low predicted toxicity. These findings highlight the potential of betacyanin-grafted inulin as a natural, colon-targeted therapeutic strategy for COX-2-mediated colon cancer, combining targeted delivery with antioxidant and anti-inflammatory properties. HIGHLIGHTS Betacyanin-grafted inulin was successfully synthesized as a targeted colon cancer therapeutic via a probiotic-responsive drug delivery system. FTIR and UV-Vis spectroscopy confirmed the structural integrity and stability of betacyanin post-grafting. Antioxidant assays showed that 0.4 g betacyanin variation retained high activity (35.08 mg/L), indicating that betacyanin remained active after grafting onto inulin Molecular docking and dynamics simulations demonstrated strong binding affinity and conformational stability of betacyanin at the COX-2 active site. ADMET profiling predicted favorable pharmacokinetics and low toxicity, supporting the therapeutic potential of betacyanin. GRAPHICAL ABSTRACT